2019
DOI: 10.1002/jcb.29285
|View full text |Cite
|
Sign up to set email alerts
|

Development of a novel six‐long noncoding RNA signature predicting survival of patients with bladder urothelial carcinoma

Abstract: Bladder urothelial carcinoma is a malignant tumor with a high incidence in the uropoietic system. Considerable studies have shown that long noncoding RNA (lncRNA) plays an important role in the development and progression of bladder urothelial carcinoma. In this study, the lncRNA expression and clinical data of 377 bladder urothelial carcinoma patients were obtained from The Cancer Genome Atlas database and differentially expressed lncRNAs in cancer and normal groups were evaluated. Univariate COX and multivar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 35 publications
(53 reference statements)
2
15
0
Order By: Relevance
“…Nowadays, many studies used high-throughput sequencing data to identify gene signatures and construct clinical predictive models. Gao et al [39] identified a 6-lncRNA signature to predict the prognosis of BCa and their AUC for 5-year survival is 0.751, which is similar to 0.742 by our signature. However, they didn't report the AUC value for 1-year survival and thus the predictive power for short-term follow-up is uncertain.…”
Section: Agingsupporting
confidence: 78%
“…Nowadays, many studies used high-throughput sequencing data to identify gene signatures and construct clinical predictive models. Gao et al [39] identified a 6-lncRNA signature to predict the prognosis of BCa and their AUC for 5-year survival is 0.751, which is similar to 0.742 by our signature. However, they didn't report the AUC value for 1-year survival and thus the predictive power for short-term follow-up is uncertain.…”
Section: Agingsupporting
confidence: 78%
“…Among those upregulated lncRNAs, lncRNA‐activating regulator of DKK1 (LNCAROD) (also named aslnc‐MBL2‐4 or LINC01468) was found to be overexpressed in HNSCC samples, which is in consistent with a previous report (Gao et al , 2014). LNCAROD is also highly expressed in bladder urothelial carcinoma and predicts unfavorable prognosis (Gao et al , 2019), suggesting an oncogenic role in cancer development. Thus, it was chosen for further validation.…”
Section: Resultsmentioning
confidence: 99%
“…Till date, no report on IRG-based prognostic signatures exists, although considerable efforts have been made to develop prognostic signatures based on differentially expressed genes (Gao et al, 2019;Yan et al, 2019;Zhang et al, 2019). We identified seven prognostic IRGs based on a comprehensive analysis which could serve as valuable biomarkers in the clinical setting.…”
Section: Discussionmentioning
confidence: 99%